2020
DOI: 10.1080/17435390.2020.1778809
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects of titanium dioxide particles on human liver, intestinal tissue, spleen and kidney after oral exposure

Abstract: Recent studies reported adverse liver effects and intestinal tumor formation after oral exposure to titanium dioxide (TiO 2). Other oral toxicological studies, however, observed no effects on liver and intestine, despite prolonged exposure and/or high doses. In the present assessment, we aimed to better understand whether TiO 2 can induce such effects at conditions relevant for humans. Therefore, we focused not only on the clinical and histopathological observations, but also used Adverse Outcome Pathways (AOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 76 publications
1
39
1
Order By: Relevance
“…For titanium dioxide (TiO 2 ) we recently postulated that high dose levels could negatively affect the uptake and subsequent effects (Brand et al 2020). We also postulated administration via the diet could negatively affect the uptake of TiO 2 , in contrast to the impression given by SAS in the present study.…”
Section: Dosing Regimen and Dispersioncontrasting
confidence: 45%
“…For titanium dioxide (TiO 2 ) we recently postulated that high dose levels could negatively affect the uptake and subsequent effects (Brand et al 2020). We also postulated administration via the diet could negatively affect the uptake of TiO 2 , in contrast to the impression given by SAS in the present study.…”
Section: Dosing Regimen and Dispersioncontrasting
confidence: 45%
“…Over the last years, an increasing number of studies investigated the behavior and effects of E171 and nano-sized TiO 2 after ingestion and discovered potential adverse effects, including the induction of inflammation, the formation of reactive oxygen species (ROS), and co-genotoxic effects [13]. Sub-acute and sub-chronic studies also revealed the induction of epithelial hyperplasia and preneoplastic lesions in the colon of rats and mice after the ingestion of E171, while other oral toxicological studies did not confirm such effects [14][15][16][17][18].…”
Section: Background Of Tio 2 As a Food Additivementioning
confidence: 99%
“…However, if toxicokinetic information based on internal organ concentration and accumulation over time of TiO 2 nanoparticles was included, the potential additional risk for liver and testis was identified [1]. Additional work of Heringa et al (2018) and Brand et al (2020) showed that post-mortem collected human liver (median 0.03 mg/kg), jejunum (median 0.14 mg/kg), ileum (median (0.26 mg/kg), kidney (median 0.06 mg/kg) and spleen (median 0.04 mg/kg) contain titanium particles and that they accumulated both micro-and nanosized TiO 2 [13,76]. The quantities detected in these organs were partially higher than levels that are considered safe for humans, after applying conventional safety factors [76].…”
Section: Heringa Et Al (2016) Andmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Abderrahim Nemmar et al concluded that iron oxide nanoparticles can caused thrombosis, cardiac oxidative and DNA damage through acute intravenous administration [ 145 ]. There are also reports that titanium dioxide nanoparticles and others nanoparticles are harmful to kidney [ 146 , 147 ]. Tungsten trioxide nanoparticles and iron oxide nanoparticles can cause liver toxicity in mice [ 148 , 149 ].…”
Section: The Limitation Of Nanomaterialsmentioning
confidence: 99%